2013
DOI: 10.9734/bjmmr/2013/1745
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria Parasitaemia and Its Association with ABO Blood Grouping among Students of Igbinedion University Okada, Nigeria

Abstract: This study was carried out to investigate ABO blood groups association with malaria parasitaemia among students of Igbinedion University, Okada located in Mid-Western Nigeria. Two milliliters (2ml) of venous blood was collected by venipuncture using 5ml hypodermic needles and syringes from 104 asymptomatic malaria students between March and June 2012. Blood samples were immediately dispensed into Ethylene Diamine Tetra-Acetic acid (EDTA) anticoagulated containers and mixed appropriately. ABO blood typing using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
14
10
2
Order By: Relevance
“…Similar conclusions have been made by previous researchers. 7,19,20 The low levels of parasitaemia with an average density of 126 parasites/µl recorded among the infected donors is similar to the values of between 10-400 parasites/µl and 285 parasites/µl of blood average reported by Chigozie JU et al and Aina OO et al respectively. 21,22 This is higher than the density of 20 obtained by Garba DD et al . However, other studies have reported higher densities of 10,000 -250,000 parasites/µl of blood.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar conclusions have been made by previous researchers. 7,19,20 The low levels of parasitaemia with an average density of 126 parasites/µl recorded among the infected donors is similar to the values of between 10-400 parasites/µl and 285 parasites/µl of blood average reported by Chigozie JU et al and Aina OO et al respectively. 21,22 This is higher than the density of 20 obtained by Garba DD et al . However, other studies have reported higher densities of 10,000 -250,000 parasites/µl of blood.…”
Section: Resultssupporting
confidence: 83%
“…3 The higher prevalence rate observed for the females in this study is in concordance with the findings of several other researchers. 19,20,23,26,27,28 This is also consistent with the assertion that females are more vulnerable to this disease in Africa. 29 The reason for higher prevalence among the females may be a reflection of differences in disease susceptibility or reporting.…”
Section: Resultssupporting
confidence: 77%
“…This finding agrees with Muntaka and Opoku-Okrah but at variance with Otajevwo who reported that more females were infected than males among students of Igbinedion University Okada, Nigeria [32,33]. The fact that more male subjects 80.4% presented as donors than females (19.6%) and the reason for this discrepancy which had been explained by Bani and Giussani's who stated that gender plays key role in the motivation to give blood may explain the reason for the variation in the prevalence of infection among this population [34].…”
Section: Determination Of Blood Groupsupporting
confidence: 91%
“…Regardless of the soaring malaria incidence in endemic regions, a certain group of individuals seem to have more immunity to malaria than others. This could be accounted by several factors including haemoglobin vari-ants, ABO blood group system and enzyme action, among others [5].…”
Section: Introductionmentioning
confidence: 99%